Feeding/Eating problems in children: Who does (not) benefit after behavior therapy? A retrospective chart review - Dumont, Eric; Jansen, Anita; Duker, Pieter C.; Seys, Daniel M.; Broers, Nick J.; Mulkens, Sandra (Frontiers in Pediatrics, 2023)
Background Treating disordered feeding at a young age reduces risks of future feeding problems, but not all children profit equally; can we define predictors of a worse prognosis? Objectives In 252 children, with a mean age of 4; 7 years (SD = 3 years; range 5 months to 17; 10 years), who had undergone behavioral day treatment in the past, several variables were investigated, retrieved from initial consultation (t1) and re-assessed at follow-up (t2). Method Logistic regressions were carried out with sex, gastro-intestinal problems, refusal of the first nutrition, syndrome/intellectual disability, Down's syndrome, autism spectrum disorder, comorbidity of medical diseases (other than gastro-intestinal problems), restrictive caloric food intake and selective food intake, as the predictor variables from t1, and age-appropriate food intake at t2 as the dependent variable. The potential role of sensory processing problems was reviewed at t2. Results About 73% had improved towards an age-appropriate food intake. Sex (boys), syndrome/intellectual disability, and a lack of varied nutritional intake at t1 were predictors of a worse prognosis. We found a small, but significant correlation between current selective eating patterns and general sensory processing problems. Conclusion Feeding disordered children, especially boys, with intellectual disabilities or selective eating patterns are at risk for not achieving an age-adequate food intake at a later age, despite behavioral treatment.